Analisis Pohon Filogenetik Genus Oryza Berdasarkan Gen matK - Yoana Marizky Siregar; Violita Violita; Afifatul Achyar (Universitas Cokroaminoto Palopo, 2026)
The genus Oryza includes both cultivated and wild rice species that play an important role in global food systems and crop improvement. These species also exhibit complex evolutionary patterns, making the study of their phylogenetic relationships essential for understanding domestication and genetic diversity. In this study, phylogenetic relationships within the genus Oryza were analyzed using chloroplast matK gene sequences through a bioinformatics approach. A total of twelve species, representing both cultivated and wild taxa, were selected from the GenBank database. Sequence alignment and tree reconstruction were carried out using MEGA version 11. The phylogenetic tree was generated using the Neighbor-Joining method with the Maximum Composite Likelihood model, and its reliability was assessed through 10,000 bootstrap replications. The results show a clear distinction between cultivated and wild Oryza species. Oryza sativa (Japonica and Indica) is closely associated with O. nivara, supported by high bootstrap values, indicating a strong evolutionary link. Meanwhile, several wild species form separate clades, suggesting earlier divergence within the genus. Overall, the matK gene proves useful for describing phylogenetic relationships at the genus level, although its ability to resolve relationships among closely related species remains limited. These findings contribute to a better understanding of the evolutionary structure of Oryza and highlight the potential importance of wild rice species in future conservation and breeding efforts.